Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1371/journal.pone.0168867
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Development in Surgery: The Health, Poverty, and Equity Impacts of Charitable Surgery in Uganda

Abstract: BackgroundThe recently adopted Sustainable Development Goals call for the end of poverty and the equitable provision of healthcare. These goals are often at odds, however: health seeking can lead to catastrophic spending, an outcome for which cancer patients and the poor in resource-limited settings are at particularly high risk. How various health policies affect the additional aims of financial wellbeing and equity is poorly understood. This paper evaluates the health, financial, and equity impacts of govern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 45 publications
0
34
0
Order By: Relevance
“…Notes: We applied the three data analysis methods to a previously published cost–effectiveness analysis of government policies and nongovernmental platforms for improving the delivery of surgical oncology services in Uganda ( Table 3 ). 5 Data envelopment analysis does not give any guidance on how to decide among the six proposed policies. Cost–effectiveness analysis and health-adapted superefficiency data envelopment analysis favour similar policies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Notes: We applied the three data analysis methods to a previously published cost–effectiveness analysis of government policies and nongovernmental platforms for improving the delivery of surgical oncology services in Uganda ( Table 3 ). 5 Data envelopment analysis does not give any guidance on how to decide among the six proposed policies. Cost–effectiveness analysis and health-adapted superefficiency data envelopment analysis favour similar policies.…”
Section: Resultsmentioning
confidence: 99%
“…We tested our health-adapted superefficiency data envelopment analysis method by applying it to data from three previously published extended cost‒effectiveness analyses of policy inteventions. 4 , 5 , 8 The first example was an analysis of policies to increase access to surgery in Ethiopia in terms of the cost, health benefits and effects on financial risk protection ( Table 1 ). The second example was a synthesis of different preventive and curative health interventions from several analyses, reporting the cost, health benefits and financial risk protection of the interventions ( Table 2 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, while the vast majority of surgical organizations incorporate training and education into their missions [ 24 ], this may be counterbalanced by stresses on local infrastructure and distortion of local health markets and systems [ 33 ]. A recent modeling study investigating the impact of nine policy changes for surgical access on health benefit, cost, and equity in Uganda found that the ‘mission trip’ platform for surgical care delivery was more expensive and less effective than nearly all other platforms studied [ 34 ]. An additional limitation of this model is the lack of harmonization that stems from multiple distinct organizations functioning within the same space without coordination of their efforts, which is a condition common in international aid and addressed by the Paris Declaration on Aid Effectiveness [ 35 ].…”
Section: Types Of Humanitarian Outreachmentioning
confidence: 99%
“…There are various models for expanding access to surgical care that include task-shifting, 22 use of mobile platforms 23 and impact of government policy, 24 but little is known regarding case-finding strategy. We sequentially evaluated two selection strategies: a centralised selection strategy that focused on the larger population centres in Madagascar and a decentralised strategy that deliberately targeted remote areas of Madagascar, where access to surgical care was limited.…”
Section: Overcoming Barriers To Surgical Access For the Most Undersermentioning
confidence: 99%